Comparative Transcript Levels of Sugar Metabolism Genes Between the Canary Melon and a Vietnamese Non-Sweet Melon Cultivar - Nguyen, Phuong Dong Tran; Nguyen, Nguyen Hoai (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
Two different melon cultivars, Canary and Vietnamese non-sweet melons, are used to compare the fruit's sweetness levels. The results indicate that the Canary melon is much sweeter than the non-sweet melon. The transcript levels of the sugar metabolism genes, including Cucumis melo ACID INVERTASE 2 (CmAIN2) and SUCROSE SYNTHASE 1 (CmSUS1), are examined in two fruit tissues. PCR using cDNA and the electrophoresis assays indicate that the CmAIN2 and CmSUS1 primer sets are specific, and only one band of PCR product is obtained from all tested samples. The quantitative reverse transcription PCR (RT-qPCR) assay is applied to compare the transcript levels of the CmAIN2 and CmSUS1 genes in fruit tissues of the Canary and the Vietnamese non-sweet melons. Consistent with the sweetness levels, the CmAIN2 and CmSUS1 transcript levels are higher in the Canary melon than those in the non-sweet melon. These results imply that the local sugar metabolism in the fruits may also play an essential role in determining fruit sweetness. In addition, practically, the transcript levels of the CmAIN2 and CmSUS1 genes can be accessed and used to predict the sweetness of melon fruits early.